Pengaruh Dukungan Sosial Suami Terhadap Perceived Stress Pada Wanita Yang Mengalami Infertilitas Dengan Self Compassion Sebagai Variabel Mediasi: Penelitian - Emmy Primasti Wirdahanum; Hasnida; Rangkuti, Rahmi Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Stress in women facing infertility is often influenced by their ability to manage themselves emotionally, including through self-compassion, as well as by the quality of social support they receive, especially from their husbands. This study aims to analyze how the influence of social support from husbands on perceived stress in women experiencing infertility is mediated by self-compassion. Data were obtained from 390 women experiencing infertility using a self-compassion scale, a husband's social support scale, and a perceived stress scale. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the mediating effect. Based on the hypothesis proposed in this study, self-compassion has a significant effect in mediating the influence of husband's social support on perceived stress in women experiencing infertility. This is evidenced by the t-statistic value of the construct being 2.964 (>1.96) and the p-value being 0.003 (<0.05). This study provides an overview of how self-compassion can mediate the effect of husband's support on perceived stress in women experiencing infertility.